Creating crystal jewelry with Swarovski 65 sparkling designs with crystal beads and stones - McCabe, Laura (Chanhassen, Minn. Creative Pub. international, Inc., 2008)
Elegant, old-world jewelry with modern style. Working with world-famous Swarovski crystal beads, author Laura McCabe creates luminous necklaces, earrings, pendants, and rings for beaders of every skill level. The author provides complete step-by-step instruction for 20 projects (10 for beginners) -- and presents 45 more in a photo gallery of design variations, teaching readers how to vary colors and shapes to create custom effects. All 65 designs are made with only three simple beadwork techniques: flat peyote stitch, tubular peyote stitch, and spiral rope. Laura McCabe also provides a chapter.
Keywords: Swarovski (Firm); Beadwork -- Patterns; Jewelry making